Fototerapeutyczna keratektomia laserowa w leczeniu uporczywego owrzodzenia rogówki powstałego po jej oparzeniu. Badania kliniczne - Lakimenko, Stanislav; Buznyk, Oleksiy; Shchypun, Sergiy (Klinika Oczna / Acta Ophthalmologica Polonica, 2010)
Purpose: To evaluate efficacy of excimer laser phototherapeutic keratectomy (PTK) in treatment of patients with post-burn persistent corneal ulcers. Material and methods: Study design – nonrandomized trial with a “historic” control group. 54 eyes (53 patient) with central superficial post-burn corneal ulcers that were formed in different time frame (18-104 days) after grade IV burns were included into the study. Among these 26 patients (26 eyes) were included prospectively – they underwent 1-time PTK. Control group consists of 27 patients (28 eyes), who underwent surgical keratectomy of ulcer edge and base. Indication for surgery in both groups was non-decreasing size of ulcer during 7-14 days of conventional treatment. Patients of both groups wore therapeutic contact lenses after surgery. Outcome measures were number of cases of corneal healing, number of complications, terms of corneal epithelialization, visual acuity. Results: PTK promoted corneal healing in 24/26 patients, surgical keratectomy was effective in 27/28 patients. PTK 1) did not lead to complications (one corneal perforation in control group), 2) accelerated corneal epithelialization on 18,4 days compared to surgical keratectomy group (p = 0.000, Kruskal-Wallis test), 3) improved mean visual acuity on 0.08 compared to control group in 6 months follow-up examination (Bonferroni corrected p = 0.002, Kruskal-Wallis test). Conclusion: PTK is a safe and effective method for treatment of post-burn superficial persistent corneal ulcers recalcitrant to conventional therapy.